Farmers' bounty : locating crop diversity in the contemporary world. - Brush, Stephen B. (Yale agrarian studies series, 2004)
Biological diversity is as crucial in agriculture as it is in nature, and it is equally important to the economic health of both industrial and nonindustrial societies. This book offers a sweeping assessment of crop diversity and the potential for its preservation. Stephen B. Brush develops a framework for investigating biological diversity in agriculture that focuses on the knowledge and practice of farmers, and he shows how this human ecology perspective can be applied to three global issues that affect crop resources.